The potential of medicinal food plant Panax ginseng C. A. Mey. in managing chronic diseases via gut microbiota regulation: a systematic review of mechanisms and evidence - Gao, Meng; Wang, Haijing; Chen, Xiaojing; Wang, Wensheng; Liu, Yongmei (Frontiers in Pharmacology, 2025)
Panax ginseng C.A. Mey. (PG), a well-documented medicinal food plant with generally recognized as safe status, exhibits therapeutic potential for managing metabolic disorders (type 2 diabetes mellitus (T2DM), obesity), inflammatory bowel diseases (IBD), and neurodegenerative conditions via modulation of the gut microbiota (GM). This systematic review of 102 studies reveals that ginsenosides (Rb1, Rg1, and Rg3) undergo biotransformation mediated by the GM into bioactive metabolites (e.g., compound K), enhancing their bioavailability by 3- to 5-fold (p < 0.01). Three core mechanisms were identified: 1) inhibition of the TLR4/NF-κB pathway reduces pro-inflammatory cytokine levels by 40%–60%; 2) upregulation of tight junction proteins (ZO-1/claudin-4) strengthens intestinal barrier function by 2.3-fold; and 3) selective GM modulation increases the relative abundance of probiotics (Lactobacillus ↑2.1-fold, Bifidobacterium ↑1.8-fold) while decreasing pathogenic bacteria (Clostridium ↓65%), collectively increasing short-chain fatty acid (SCFA) production by 3.2-fold, and activating AMPK/SIRT1 signaling. Clinical evidence supports PG’s efficacy: 15.2% reduction in fasting blood glucose levels in T2DM, 28.5% decrease in diamine oxidase (DAO) activity in IBD, and improvements in cognitive function scores (Mini-Mental State Examination scores increased by 2.4 points) in mild cognitive impairment. Emerging research further reveals a “microbiota-gut-brain axis” mediated by GM-derived metabolites acting via G protein-coupled receptors (GPCRs) and vagal pathways.